SOSIALISASI DAN PELATIHAN PEMBUATAN MINUMAN NUTRASEUTIKAL SERTA PEMERIKSAAN KESEHATAN DI DESA MENINTING, KABUPATEN LOMBOK BARAT - Muliasari, Handa; Permatasari, Lina; Dewi, Ni Made Amelia Ratnata; Saputra, Yoga Dwi; Nirmala, Annisa Rizka; Hafizah, Qori’atul; Ananta, Muhammad Naufal Farras; Farobbi, Muhammad Iqbal; Kabir, Mila Mayanti; Alya, Ainun; et al. (Jurnal Pepadu, 2024)
Consuming healthy foods such as nutraceuticals or functional foods is very important to prevent and reduce the risk of degenerative and chronic diseases. Efforts to improve community knowledge and skills related to nutraceuticals are very important, so community service activities are carried out with the aim of providing socialization and training on the production of nutraceutical drinks from local natural ingredients, as well as health checks including blood pressure, blood sugar, cholesterol and uric acid. The partners of this community service activity are PKK women and the community in Kongok Hamlet, Meninting Village, Batulayar District, West Lombok Regency, NTB. The community service activities consist of several stages, namely activity preparation, location survey and coordination with partners, socialization of nutraceutical drinks using PowerPoint slides and leaflets, training on the production of nutraceutical drinks, health checks, and ending with post-tests and activity evaluations using questionnaires. The 56 residents who attended were very enthusiastic in participating in the activities. The results of the questionnaire showed that 35.7% of the participants who attended were able to answer questions related to the socialization material with an average score of 74.3. The results of the activity evaluation questionnaire stated that activities like this are very important to do and the selection and provision of material are very good and clear. Thus, it can be concluded that this community service activity is very beneficial for the community and the socialization and training materials can be understood well by the participants of the community service activity.